Development and assessment of renewable hydrogen production and natural gas blending systems for use in different locations - Sorgulu, Fatih; Dincer, Ibrahim (WILEY, 2022)
In this study, a thermoeconomic assessment of renewable energy-based hydrogen generation and blending it with natural gas in the existing pipeline system is performed for various locations. Selected locations are compared in energy content, environmental impact, and cost. In this regard, solar photovoltaic panels and wind turbines are integrated with electrolyzers along with the reverse osmosis units. The clean hydrogen produced by the electrolyzers is then blended with natural gas and utilized for residential applications in an environmentally benign way. Also, the heat required for a community consisting of 100 houses is provided by a boiler by hydrogen and natural gas blend as fuel. The costs of capital, fuel, operation and maintenance are calculated and comparatively evaluated. The results show that the total net present costs for the integrated systems are calculated to be between $3.01 million and $4.36 million in the selected five different locations. Furthermore, an environmental impact assessment is conducted in terms of carbon monoxide, carbon dioxide, nitrogen oxides, unburned hydrocarbons, and particulate matter. Finally, the CO2 emissions are calculated to be varying from 443.2 to 491.9 tons/year.
Keywords: cost; efficiency; emissions; hydrogen; natural gas; solar energy; wind energy; Energy & Fuels